Confinement of an electron-capturing unit within an electron-donating framework for X-ray detection. Issue 16 (29th March 2016) - Zhang, Hao; Sheng, Tianlu; Hu, Shengmin; Zhuo, Chao; Fu, Ruibiao; Wen, Yuehong; Li, Haoran; Wu, Xintao
Abstract : A novel X-ray-induced photochromic metal–organic complex was constructed by confining an electron-capturing unit within the cavity of an electron-donating framework. Abstract : A novel X-ray-induced photochromic metal–organic complex (cMOC-3) was constructed by confining an electron-capturing unit within the cavity of an electron-donating framework. Photochromic transformation from pale yellow to blue under X-ray irradiation was reversible, and recovered by thermal treatment. These phenomena can be attributed to metal-assisted ligand to ligand charge transfer (LLCT) between the electron-deficient unit and the electron-donating framework. Additionally, such a charge transfer process is responsible for switchable fluorescence regulated by X-ray irradiation with high photo-fatigue resistance. The X-ray-induced photochromism and fluorescence modulation opens a new avenue for developing convenient and quick-responsive smart optical materials for X-ray detection.